Determination and thermodynamic modelling for 2-methyl-6-nitroaniline solubility in binary solvent mixtures of ethyl acetate + (methanol, ethanol, n-propanol and isopropanol). (February 2017) - Cong, Yang; Du, Cunbin; Wang, Jian; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of 2-methyl-6-nitroaniline in four binary mixed solvents were determined. Solubility data were correlated and calculated by six models. The standard dissolution enthalpy for the dissolution processes were computed. Abstract: The solubility of 2-methyl-6-nitroaniline in binary mixed solvents of (ethyl acetate + methanol), (ethyl acetate + ethanol), (ethyl acetate + n -propanol) and (ethyl acetate + isopropanol) was determined experimentally by using the isothermal dissolution method within the temperature range from (278.15–313.15) K under atmosphere pressure. The solubility of 2-methyl-6-nitroaniline increased with increasing temperature and mass fraction of ethyl acetate in each binary system. At the same temperature and mass fraction of ethyl acetate, the mole fraction solubility of 2-methyl-6-nitroaniline was greater in (ethyl acetate + n -propanol) than in the other three mixed solvents. The achieved solubility values were correlated by employing Jouyban-Acree model, van't Hoff-Jouyban-Acree model, Apelblat-Jouyban-Acree model, Ma model, Sun model and CNIBS/R-K model. The values of relative average deviations ( RAD ) and root-mean-square deviations ( RMSD ) were no greater than 1.79% and 20.56 × 10 −4 for the six models. In general, the Jouyban-Acree model proved to provide better representation of the experimental solubility. Furthermore, the dissolution enthalpies of the dissolution process were calculated. Positive values of dissolution enthalpy showed that the dissolution process of 2-methyl-6-nitroaniline in these mixed solvents was endothermic. The experimental solubility results and models presented in the present work are essential in the practical process for production and purification of 2-methyl-6-nitroaniline.